INDONESIAN BANKING PERFORMANCE OF PRE AND POST OF MERGERS AND ACQUISITIONS - Mustaruddin Saleh (TRIKONOMIKA, 2022)
The objective of this study to analyse the performance of banks before and after conducting Mergers and Acquisitions (M&A) using a risk approach and how it affects the value of banking companies. Banking performance was analysed from three years before and three years after conducting mergers and acquisitions. To analyse the impact of banking mergers and acquisitions on company value, paired sample t-test and the fixed effect model (FEM) and Random Effect Model (REM) are utilised to test the research hypothesis. The results show that the banking performance after conducting M&A is decreased. This is demonstrated by the improvement in banking value and performance by using variables PBV, Tobin’s q, LDR and COMIN, which increase relatively after mergers and acquisitions, but the ability to generate profits, as measured by ROA is decreased.This is an implication of the combination of large assets that have not been used optimally to generate profits.